2014
DOI: 10.1021/ja509307m
|View full text |Cite
|
Sign up to set email alerts
|

Type-II CdSe/CdTe Core/Crown Semiconductor Nanoplatelets

Abstract: We have synthesized atomically flat CdSe/CdTe core/crown nanoplatelets (NPLs) with thicknesses of 3, 4, and 5 monolayers with fine control of the crown lateral dimensions. In these type-II NPLs, the charges separate spatially, and the electron wave function is localized in the CdSe core while the hole wave function is confined in the CdTe crown. The exciton's recombination occurs across the heterointerface, and as a result of their spatially indirect band gap, an important emission red shift up to the near-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
296
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(318 citation statements)
references
References 58 publications
(103 reference statements)
22
296
0
Order By: Relevance
“…34 Since our platelets have a relatively large lateral size and hence increased coherence volume, 34,47 the GOST effect also leads to shorter lifetimes compared to ref. 41. Due to relatively high PL quantum yield in our samples (23%) for the 5 ML CdSe-CdTe hetero-NPLs we can definitely exclude the idea that the observed fast exciton lifetimes in our type-II hetero-NPLs result from dominating non-radiative processes since τ dec = τ rad ·QY, so that the measured decay time τ dec cannot be considerably smaller than the radiative lifetime τ rad .…”
Section: Pl Lifetime Measurementsmentioning
confidence: 69%
See 2 more Smart Citations
“…34 Since our platelets have a relatively large lateral size and hence increased coherence volume, 34,47 the GOST effect also leads to shorter lifetimes compared to ref. 41. Due to relatively high PL quantum yield in our samples (23%) for the 5 ML CdSe-CdTe hetero-NPLs we can definitely exclude the idea that the observed fast exciton lifetimes in our type-II hetero-NPLs result from dominating non-radiative processes since τ dec = τ rad ·QY, so that the measured decay time τ dec cannot be considerably smaller than the radiative lifetime τ rad .…”
Section: Pl Lifetime Measurementsmentioning
confidence: 69%
“…Similar behaviour was observed earlier for 4 and 5 ML CdSe-CdTe hetero-NPLs prepared by different protocols. [41][42][43] The PL quantum yield of our 5 ML CdSe-CdTe HNPLs, measured at room temperature in chloroform relative to Rhodamine 6G in ethanol, was 23%. This is a rather high value for the HNCs with an indirect optical transition schematically shown in Fig.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Also, it was shown that higher concentration of OA results in formation of extended CdTe crown region and enhances the absorption of crown region. 34 However, for the CdSe/CdTe core/crown NPLs synthesized by using an excess amount of TOP ( Figure S1 in the Supporting Information), the excitonic peak corresponding to 4 ML thick CdTe crown layer could not observed clearly, which can be attributed to the nonuniform and/or partial coating of CdTe crown region. Moreover, an absorption tail extending into the lower energy side of the absorption spectra is observed, and this can be attributed to the intermediate transitions at the core/crown interface owing to the Type-II band alignment.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently, during the review process of our work, the report by Pedetti et al appeared to show the synthesis and characterization of CdSe/ CdTe core/crown NPLs having Type-II electronic structure using a different cadmium precursor. 34 Here, in an independent study, we report the synthesis of CdSe/CdTe core/crown NPLs having Type-II electronic structure with varying crown width by using core-seeded lateral shell growth approach. With the laterally grown CdTe crown region, atomically flat CdSe/CdTe core/crown NPLs are achieved, which is highly promising for efficiently removal of excited carriers.…”
Section: ■ Introductionmentioning
confidence: 99%